Front Cover: Optimization of headspace for GC‐MS analysis of fragrance allergens in wooden children's products using response surface methodology. Issue 1 (25th January 2019) - Li, Meiping; Li, Rong; Wang, Zhijuan; Zhang, Qing; Bai, Hua; Lv, Qing
Abstract : Sep Sci plus 2019;2:26–37. DOI:10.1002/sscp.201800125 The cover picture shows a headspace extraction method for determining 48 fragrance allergens in wooden children's products. Minimal amounts of sample and acetone solvent were used, and no additional pretreatment was performed except for freezing and grinding. Three factors (incubating temperature, equilibration time, pressing pressure) affecting HS extraction were optimized by response surface methodology to obtain scientific results considering of the interactions among variables. A dynamic equilibrium of fragrances was achieved under the vapor atmosphere of solvent, which allowed the fragrances in the samples to be measured by GC‐MS.